SISTEM PENGETAHUAN LOKAL DAN PEMBANGUNAN BERKELANJUTAN - Imanta Immanuel Perangin-Angin (Jurnal Pluralis, 2024)
The development carried out by almost all countries has become a global force that is almost unstoppable, especially in efforts to increase people's welfare and increase state revenues, especially for the running of a country's government. But then it was realized that the development was also a source of threats to damage to the earth and environmental disasters. This is what later became the originator that needed a development that is sustainable in nature which of course involves the local community. The existing local knowledge system is expected to be able to become a knowledge of the development model that will be applied so that later the local community is involved in the process, starting from planning, procuring communal capital and sharing benefits from a sustainable development activity.